Vesicoprostatic Rhabdomyosarcoma in an 8-Month-Old Infant: Case Report - Safari, Kunaba D; Segbedji, G. G. P. S.; Lafia, K. T.; Amoussou, C. A.; Muhindo, Mutuka H.; Fiogbé, M. A. (British Journal of Healthcare and Medical Research, 2023)
Introduction: Rhabdomyosarcoma (RMS) is the most common malignant mesenchymal tumor of children and adolescents. The vesicoprostatic form is rare in the urogenital location, which represents 25% of the preferred sites of RMS, with acute retention of urine as the inaugural sign. Case presentation: we report the case of an 8-month-old male infant seen for an abdominal mass with dysuria. Surgery consisted of radical excision of the tumor followed by chemotherapy. Histological examination of the tumor confirmed a botryoid embryonal rhabdomyosarcoma. Progression under chemotherapy was favorable with complete remission. Conclusion: the rhabdomyosarcoma is chemosensitive tumors, management is multidisciplinary, combining surgery, chemotherapy, radiotherapy and brachytherapy. These tumors have a good prognosis due to their anatomical accessibility and good response to chemotherapy.